The Influence of Bank Performance on Bank-Spesific, Industry-Spesific, Macroeconomic Factors and Income Diversification in Banking Sectors - Sijabat, Elpha Yuli; Suprapto, Agung; Henny Setyo Lestari, I Nyoman Dipa Swagotra Harijaya , Farah Margaretha, (SEIKO : Journal of Management & Business, 2024)
This study aims to analyze the impact of bank-specific factors, industry-specific factors, macroeconomic factors, and income diversification on the performance of 36 commercial banks listed on the Indonesia Stock Exchange. A quantitative method is applied, using secondary data from financial statements of commercial banks for the period 2018-2022. The dependent variables measured are Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM). Panel regression analysis is used to examine the influence of these factors on bank performance. The findings indicate that asset quality and inflation have a significant impact on ROA and ROE, while the loan ratio significantly affects ROE. Meanwhile, factors such as asset share, deposit share, and loan share do not show a significant influence. For the NIM variable, inflation and average exchange rates have a significant impact. This study is limited by the use of secondary data, which reflects only the conditions of companies listed on the Indonesia Stock Exchange, so the results cannot be generalized to all banks. Practically, this study can assist bank management in understanding the factors influencing financial performance and in making informed decisions based on relevant macroeconomic conditions. This study offers a novel contribution in identifying the relationship between bank-specific and macroeconomic factors with banking performance in Indonesia. Keyword: bank performance, bank-spesific, industry-spesific, macroeconomic, income diversification.